2009
DOI: 10.1103/physrevd.80.023528
|View full text |Cite
|
Sign up to set email alerts
|

Generalized DBI quintessence

Abstract: We investigate the phase space of a quintessence theory governed by a generalised version of the DBI action, using a combination of numeric and analytic methods. The additional degrees of freedom lead to a vastly richer phase space structure, where the field covers the full equation of state parameter space; −1 ≤ ω ≤ 1. We find many non-trivial solution curves to the equations of motion which indicate that DBI quintessence is an interesting candidate for a viable k-essence model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 76 publications
2
39
0
Order By: Relevance
“…In the presence of a non-Bogomolnyi-Prasad-Sommerfield (BPS) brane or multiple D 3 -branes, the DBI action acquires an additional potential U multiplying the DBI term [49,50]. U can arise in different places within the theory.…”
Section: The New General Lagrangian Of Dbi Inflationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of a non-Bogomolnyi-Prasad-Sommerfield (BPS) brane or multiple D 3 -branes, the DBI action acquires an additional potential U multiplying the DBI term [49,50]. U can arise in different places within the theory.…”
Section: The New General Lagrangian Of Dbi Inflationmentioning
confidence: 99%
“…For U (φ) = 1, the Equation (51) can be reduced into the Klein-Gordon equation in [49]. Let us consider the scenario by using Equations (22), (23) and the general DBI inflation Lagrangian Equation (10), we deduce the equation of states…”
Section: Dark Energy With Dbi Inflationmentioning
confidence: 99%
“…Within the context of string theory there is a model for the early-time accelerated expansion of the Universe associated with inflation. This string-theorymotivated model for inflation is called Dirac-Born-Infield (DBI) inflation [6][7][8][9][10][11], and it is driven by the open string sector through dynamical Dp-branes. DBI inflation is a special case of K-inflation models [12].…”
mentioning
confidence: 99%
“…DBI inflation is a special case of K-inflation models [12]. It was originally thought that DBI inflation models would yield large non-Gaussian perturbations which could be used to verify or falsify these models and by extension to test string theory [11,13]. However, subsequent work has shown that this may not be the case, and that the simplest DBI models are effectively indistinguishable from standard fieldtheoretic slow-roll models of inflation [14].In the present work we examine variants of these DBI models as a mechanism, not for the early-time acceleration of inflation, but for the observed late-time accel-…”
mentioning
confidence: 99%
“…These usually include k-essence, dilaton, DBIessence, Hessence, tachyon, Chaplygin gas, etc. [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%